Is the time right for in vitro neurotoxicity testing using human iPSC-derived neurons? - Tukker, Anke (ALTEX, 2016)
Current neurotoxicity testing heavily relies on expensive, time consuming and ethically debated in vivo animal experiments that are unsuitable for screening large number of chemicals. Consequently, there is a clear need for (high-throughput) in vitro test strategies, preferably using human cells as this increases relevance and eliminates the need for interspecies translation. However, human stem cell-derived neurons used to date are not well characterised, require prolonged differentiation and are potentially subject to batch-to-batch variation, ethical concerns and country-specific legislations. Recently, a number of human induced pluripotent stem cell (iPSC)-derived neurons became commercially available that may circumvent these concerns. We therefore used immunofluorescent stainings to demonstrate that human iPSC-derived neurons from various suppliers form mixed neuronal cultures, consisting of different types of (excitatory and inhibitory) neurons. Using multi-well microelectrode array (mwMEA) recordings, we demonstrate that these human iPSC-derived cultures develop spontaneous neuronal activity over time, which can be modulated by different physiological, toxicological and pharmacological compounds. Additional single cell calcium imaging illustrates the presence of functional GABA, glutamate, and acetylcholine receptors as well as voltage-gated calcium channels. While human iPSC-derived neuronal cultures appear not yet suitable to fully replace the rat primary cortical model, our data indicate that these rapidly differentiating, commercially available human iPSC-derived neuronal cultures are already suitable for in vitro prioritisation and effect screening studies. Further characterisation and toxicological validation is now required to facilitate acceptance and large-scale implementation of these animal-free, physiologically-relevant human iPSC-based modelsfor future neurotoxicity testing.